Evaluation of errors related to surgical pathology specimens of different hospital departments with a patient safety approach: a case study in Iran - Seyed Saeed Tabatabaee; Vahid Ghavami; Rohollah Kalhor; Mohammad Amerzadeh; Hadi Zomorrodi-Niat (Patient Safety in Surgery, 2023)
Abstract Background Most surgical specimen errors occur in the pre-analysis stage, which can be prevented. This study aims to identify errors related to surgical pathology specimens in one of the most comprehensive healthcare centers in Northeast Iran. Methods The present study is descriptive and analytical research conducted cross-sectionally in 2021 at Ghaem healthcare center in the Mashhad University of Medical Sciences on the basis of a census sampling. We used a standard checklist to collect information. Professors and pathologists evaluated the validity and reliability of the checklist using Cronbach’s alpha calculation method of 0.89. We analyzed the results using statistical indices, SPSS 21 software, and the chi-square test. Results Out of 5617 pathology specimens studied, we detected 646 errors. The highest number of errors is the mismatch of the specimen with the label (219 cases; 3.9%) and the non-compliance of the patient’s profile in the specimen sent with the label (129 cases; 2.3%), and the lowest errors are the inappropriate volume of the fixator(24 cases; 0.4%), and they accounted for insufficient sample size (25 cases; 0.4%). Based on Fisher’s exact test results, there was a significant difference between the proportion of errors in different departments and months. Conclusion Considering the frequency of labeling errors in the stage before the analysis in the pathology department, the use of barcode imprinted in specimen containers, the removal of the paper request for pathology, the use of radio frequency chip technology, the use of the rechecking system and improving communication in different departments can be effective in reducing these errors.